The effect of Beverages on Color Stability of Highly Impact Acrylic Resin - Ammar Kh. Al-Noori (University of Mosul, College of Dentistry, 2015)
Aim: To evaluate the effect of beverages (Distilled water ,Artificial orange, Zamzam water, Natural orange, Cola, coffee, and Tea) on the color stability of the highly impact resin. Materials and methods: Total samples of this research were (48) samples of highly impact resin were prepared 30 * 20 * 1.5 mm (length, width and thickness). Six samples were immersed in each type of beverage. The last six sample (control) without any type of beverage (after control group and other beverage groups were evaluated after (3 hours, 9 hrs, 18 hrs, 36.5 hrs, and 73 hrs) immersion time intervals by using (CIE L* a* b* ) system. the results of this research were analyzed statistically by ANOVA and Duncan's multiple range test. Results : There was no significant difference among beverages at immersion time intervals (3 hrs, 9 hrs, 18 hrs, and 73 hrs) except at (36.5 hrs) there was a significant difference, also the results showed that there was no significant difference among immersion time intervals for different types of bever-ages. Conclusions: among beverages coffee and tea showed unaccepted value of ΔE at all immersion time intervals except at (9 hrs) while cola showed an accepted values of ΔE except at (3 hrs) of immer-sion where ΔE value was unaccepted.